Tumor Microenvironment Regulation and Cancer Targeting Therapy Based on Nanoparticles - Shulan Han; Yongjie Chi; Zhu Yang; Juan Ma; Lianyan Wang (Journal of Functional Biomaterials, 2023)
Although we have made remarkable achievements in cancer awareness and medical technology, there are still tremendous increases in cancer incidence and mortality. However, most anti-tumor strategies, including immunotherapy, show low efficiency in clinical application. More and more evidence suggest that this low efficacy may be closely related to the immunosuppression of the tumor microenvironment (TME). The TME plays a significant role in tumorigenesis, development, and metastasis. Therefore, it is necessary to regulate the TME during antitumor therapy. Several strategies are developing to regulate the TME as inhibiting tumor angiogenesis, reversing tumor associated macrophage (TAM) phenotype, removing T cell immunosuppression, and so on. Among them, nanotechnology shows great potential for delivering regulators into TME, which further enhance the antitumor therapy efficacy. Properly designed nanomaterials can carry regulators and/or therapeutic agents to eligible locations or cells to trigger specific immune response and further kill tumor cells. Specifically, the designed nanoparticles could not only directly reverse the primary TME immunosuppression, but also induce effective systemic immune response, which would prevent niche formation before metastasis and inhibit tumor recurrence. In this review, we summarized the development of nanoparticles (NPs) for anti-cancer therapy, TME regulation, and tumor metastasis inhibition. We also discussed the prospect and potential of nanocarriers for cancer therapy.